Do You Know What Your Kids Are Drinking? Evaluation of a Media Campaign to Reduce Consumption of Sugar-Sweetened Beverages. Issue 6 (July 2018) - Bleakley, Amy; Jordan, Amy; Mallya, Giridhar; Hennessy, Michael; Piotrowski, Jessica Taylor
Objective: This study evaluates a citywide media campaign that targeted reducing sugar-sweetened beverage (SSB) consumption as a strategy for addressing obesity. Design: Rolling cross-sectional survey data, collected before and during the media campaign, with 1367 parents to assess exposure to and effect of a televised public service advertisement (TV PSA) developed using a reasoned action approach. Setting: Televised public service advertisement campaign created by the Philadelphia Department of Public Health and disseminated on cable television channels within the Philadelphia market. Participants: Philadelphia parents/primary caregivers with a child between the ages of 3 and 16. Results: Linear regression analysis shows that exposure to the TV PSA was significantly associated with intention to substitute nonsugary drinks for SSBs for the parent ( P = .04) and the child ( P = .02). The effect of exposure on intention to reduce child's SSB consumption increased the longer the campaign was in the field. Exposure was also significantly associated with the belief that reducing SSB consumption decreases the risk of diabetes ( P = .04) and was significantly negatively related to the belief that reducing SSB consumption would make mealtimes less enjoyable ( P = .04). Conclusion: These findings suggest that a theory-based mass media campaign can achieve positive changes in intention related to SSB consumption by changing relevant and salient underlying beliefs.